The Business of Hotels / Fourth Edition - Ingram H; Medlik S (Butterworth Heinemann, 1994)
The authors examine the hotel comprehensively as a business providing commercial hospitality. Staying away from Home, (SJr(Btel Products and Markets, Hotel Policies and Philosophies and Strategies, The Small Hotel, Hotel Groups, International Hotel Operations, Rooms and Beds, Food and Drink, Miscellaneous Guest Services, Marketing, Property Ownership and Management, Finance and Accounts, Hotel Organization, Hotel Staffing, Performance in Hotels.s